Dietary energy and crude protein requirements of Ettawah Cross Kids: 1. Intake, digestibility, availability and utilization of nutrients - Mathius, I-W; Gaga, I.B; Sutama, I-K (Indonesian Journal of Animal and Veterinary Sciences, 2002)
An experiment was designed in order to study the crude protein and energy requirement of Ettawah Cross growing goats. Twenty seven kids (average body weight of 11.80 + 1.4 kg) were used and randomly allotted to a 3 x 3 factorial arrangement of treatments, consisting of three different levels of crude protein and three levels of energy. Results from this experiment showed that animal performance was effected by dietary treatments. Increasing levels of energy ration significantly (P<0.05) decreased the dry matter intake, with overall mean values were 3.0; 2.8 and 2.5% of body weight for low, medium and high levels of energy respectively. Dietary treatments increased energy (EM) and crude protein intake, and overall values were 0.2046 + 0.016 Mkal/kg BW0.75 and 8.20 + 2.473 g/kg BW0.75 repectively. Positive response on animal performance was also effected by dietary treatment, with overall mean value of 86.40 + 29.59 g head-1day-1. The highest response on animal performance (ADG 123.3 g) was found on kids fed diet containing combination of low level of energy and high level of crude protein. Meanwhile, the lowest average daily gain (45 g) was resulted by kids fed ration containing combination of high level of energy and low level of crude protein. Â  Key words: Protein-energy, etawah cross kids, growing fase